1977
DOI: 10.1029/ja082i001p00155
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a structured auroral field-aligned current system

Abstract: A rocket-borne experiment package was launched over a structured auroral arc from Poker Flat, Alaska, at 0722 UT on February 25, 1972. The results of the flight vector magnetometer data have been detailed by Casserly and Cloutier (1975), who report the detection of a pair of oppositely directed Birkeland current sheets associated with the auroral band. This association has now been extensively investigated, and it has been shown that some observed structures in the arc due to the presence of a fold are also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Subsequently, the magnetic effects of the gross field-aligned current configuration associated with the auroral oval were reported by Zmuda et al [1967], and their spatial structure and diurnal behavior were described by Zmuda et al [1970], Armstrong and Zmuda [1970], Armstrong [1974], Zmuda and Armstrong [1974a, b], Berko et al [1975], and Sugiura [1975]. At the same time it was realized that field-aligned currents flowed in the region of discrete auroral arcs, and detailed studies of these current systems were carried out by using rocket-borne detectors [e.g., Cloutier et al, 1970Cloutier et al, , 1973Choy et al, 1971;Park and Cloutier, 1971;Vondrak et al, 1971;Whalen and McDiarmid, 1972;Arnoldy and Choy, 1973;Bryant et al, 1973;Maehlum and Moestue, 1974;Bosqued et al, 1974: Anderson andCloutier, 1975;Et•ans et al, 1917;Carlson and Kelley, 1977;Casserly, 1977] and by using satellite detectors [e.g., Hoffman and Evans, 1968;Hultqt•ist et al, 1971;Aubry et al, 1972; In the past, unambiguous conclusions based on correlative studies involving satellite and ground-based data have been difficult to achieve. This stems from the fact that ground-based instrumentation evaluates parameters which are averaged over scale sizes of hundreds to thousands of kilometers, while satellite instrumentation often provides in situ measurements pertaining to conditions in the immediate vicinity of the spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the magnetic effects of the gross field-aligned current configuration associated with the auroral oval were reported by Zmuda et al [1967], and their spatial structure and diurnal behavior were described by Zmuda et al [1970], Armstrong and Zmuda [1970], Armstrong [1974], Zmuda and Armstrong [1974a, b], Berko et al [1975], and Sugiura [1975]. At the same time it was realized that field-aligned currents flowed in the region of discrete auroral arcs, and detailed studies of these current systems were carried out by using rocket-borne detectors [e.g., Cloutier et al, 1970Cloutier et al, , 1973Choy et al, 1971;Park and Cloutier, 1971;Vondrak et al, 1971;Whalen and McDiarmid, 1972;Arnoldy and Choy, 1973;Bryant et al, 1973;Maehlum and Moestue, 1974;Bosqued et al, 1974: Anderson andCloutier, 1975;Et•ans et al, 1917;Carlson and Kelley, 1977;Casserly, 1977] and by using satellite detectors [e.g., Hoffman and Evans, 1968;Hultqt•ist et al, 1971;Aubry et al, 1972; In the past, unambiguous conclusions based on correlative studies involving satellite and ground-based data have been difficult to achieve. This stems from the fact that ground-based instrumentation evaluates parameters which are averaged over scale sizes of hundreds to thousands of kilometers, while satellite instrumentation often provides in situ measurements pertaining to conditions in the immediate vicinity of the spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…particle detectors (0.5<E<20keY) was only 17% of that inferred from the on boardd magnetometer data, suggesting that low energy electrons might play an important role as current carriers. In a subsequent paper, CASSERLY (1977) showed that the rocket magnetometer observations were best described by a double sheet current system with a poleward step to the east of the rocket ground track. SESIANO and CLOUTIER (1976) have studied magnetometer data from a rocket launched into a multiple arc system, and found evidence for three pairs of antiparallel current sheets associated with the dis- proposed by VoNDRAK (1975).…”
Section: Currents Into Ionospherementioning
confidence: 99%